The Role of T-Type Calcium Channel Genes in Absence Seizures - Chen, Yucai; Parker, William Davis; Wang, Keling (Frontiers in Neurology, 2014)
The thalamic relay neurons, reticular thalamic nucleus, and neocortical pyramidal cells form a circuit that sustains oscillatory burst firing, and is regarded as the underlying mechanism of absence seizures. T-type calcium channels play a key role in this circuit. Here we review the role of T-type calcium channel genes in the development of absence seizures, and emphasize gain or loss of function mutations, and other variations that alter both quantity and quality of transcripts, and methylation status of isoforms of T-type calcium channel proteins might be of equal importance in understanding the pathological mechanism of absence seizures.